If you're afraid of the dark, remember the night rainbow - Edens, Cooper (New York : Simon & Schuster Books for Young Readers, 1979)
Presents advice for a variety of fantastic or whimsical situations, including what to do if the sky falls, or the sun never shines again.
Keywords: Fantasy